Preparatory Knee Flexion-Extension Movements Enhance Rapid Sidestepping Performance in Collegiate Basketball Players - Fujimoto, Masahiro; Uchida, Eri; Nagano, Akinori; Rogers, Mark W.; Isaka, Tadao (Frontiers in Sports and Active Living, 2021)
Lower-limb weight-bearing load distribution in stationary standing influences the timing of rapid first step initiation of importance for functional movement activities and agility performance in sports. This study investigated the effect of pre-step lower-limb loading and unloading with preparatory knee flexion-extension movements on sidestepping performance in fifteen male collegiate basketball players. Participants performed two-choice (step limb) reaction time sidestepping under two conditions: without preparatory movements before the go cue (no-prep–NP) and with continuous alternating knee extension and flexion movements (prep–P). The reaction signal was provided at the beginning of knee extension and flexion and during these movements which corresponded with the largest and smallest loading instants and the transition states between those instants. Sidestepping performance was assessed with three-dimensional kinematic data and ground reaction forces. Step initiation onset time was significantly faster by 13–15% than the NP condition when initiated in the knee flexion phase (p ≤ 0.028, r ≥ 0.70), whereas step-limb unloading interval from step initiation to step lift-off was significantly faster by 12–15% in the knee extension phase (p ≤ 0.01, r ≥ 0.74). The preparatory movements significantly shortened step lift-off by 10–12% (p ≤ 0.013, r ≥ 0.73) and step duration by 17–21% (p < 0.001, r ≥ 0.85) with 19–22% faster step velocity (p < 0.001, r ≥ 0.84), which resulted in 14–15% shorter overall time to step landing (p < 0.001, r ≥ 0.84), irrespective of the loading phases. These results indicated that lower-limb loading with pre-step knee flexion facilitated faster step initiation, while lower-limb unloading with knee extension facilitated faster step-limb unloading, both resulting in faster step lift-off. Bilateral knee flexion-extension movements as a preparatory action could be utilized by invasion sports players to facilitate reactive stepping performance for more effective movement initiation.